Pengomposan Beberapa Macam Hasil Samping Perkebunan Sawit (Tankos dan Daun) dengan Berbagai Dekomposer : Composting Several Kinds of Palm Plantation Side Products (Tankos and Leaves) with Various Decomposers - ryan, Ryan Firman Syah; Sinurat, Azwaer Tri Ivani; Himawan, Achmad (Politeknik Negeri Cilacap, 2024)
ABSTRACT This research examines the potential of oil palm leaves as raw material for compost, carried out in Bandar Pasir Mandoge Village, North Sumatra, from March to May 2023, using a Completely Randomized Design (CRD) with two main factors: compost material and type of decomposer. The compost material consists of tankos, leaves, and a mixture of tankos+leaves, while the decomposer consists of decomposers D1, D2, and D3. The parameters measured include C/N ratio, weight loss, compost color, compost odor, compost pH value, compost temperature, compost humidity, and compost friability. The research results showed significant variations in C/N ratio values ​​for organic materials, with values ​​ranging from 12 to 38. Compost material from leaves with D1 decomposer achieved the lowest C/N ratio value, while tankos compost with D1 decomposer had the highest value. Decomposer D2 is more effective in speeding up the decomposition process compared to D1 and D3. The fastest compost shrinkage occurred in the treatment with D3 decomposer, while the longest shrinkage occurred in the treatment with D1 decomposer. This research supports the principles of sustainable agriculture by utilizing high fiber organic waste and reducing environmental pollution. Tankos organic material decomposes the fastest, and the D2 decomposer is more effective than other decomposers. There is a real interaction between organic materials and decomposers on compost quality. Keywords: Tankos, leaves, compost, decomposer